Wave propagation along an edge of a solid - PAJEWSKI, Wincenty; SZALEWSKI, Marek; KIEŁCZYŃSKI, Paweł (Archives of Acoustics, 1986)
Investigation results of waves propagating along edges of isotropic and anisotropic bodies are presented in this paper. Also methods of producing wave-guides, generation methods of line waves, the influence of anisotropy on distribution of vibrations and applications of these waves in the acoustic convolution process are discussed.